Melacur Sebagai Eksistensi Tokoh ‘Saya’ dalam Cerpen “Istri yang Tidak Pulang” Karya Djenar Maesa Ayu - Wijianti, Ardia Septi; Rusliawati, Ely (Ruang Kata, 2025)
The short story “Istri yang Tidak Pulang” by Djenar Maesa Ayu, published in 2005, presents a narrative of resistance against the social constructs that restrict women’s autonomy, particularly in relation to the body, sexuality, and the institution of marriage. The protagonist, referred to as “Saya” (I), challenges dominant discourses that deem divorce and female sexuality as taboo. By leaving her husband and choosing to become a sex worker, she attempts to reclaim control over her body and subjectivity. This act is interpreted as a search for existential selfhood, in which the female character transforms from a passive object within a patriarchal structure into a conscious, autonomous subject who actively shapes her identity. This study employs a descriptive qualitative method through close textual reading and literature review. The analysis is grounded in Simone de Beauvoir’s existentialist framework, focusing on her concepts of the Other (L’Autre) and mauvaise foi (bad faith), to examine how the protagonist negotiates her identity and bodily agency within a patriarchal society. The findings reveal that the short story portrays a woman’s effort to assert her existence through her body, despite being haunted by internalized guilt and social stigma. The protagonist’s choice to engage in sex work is not viewed as a moral downfall, but rather as an act of resistance and existential liberation. It reflects an assertion of bodily autonomy and a rejection of the objectified role traditionally assigned to women. Consequently, the story provides a critical lens on societal norms and opens new space for reading Indonesian women’s literature as a site of struggle for identity, autonomy, and subjectivity in the face of deeply entrenched gender ideologies